KESANTUNAN BERBAHASA INDONESIA SISWA SEKOLAH DASAR NEGERI 06 KOTA BENGKULU - Hambali, Daimun; Novia, Novia (Jurnal PGSD, 2017)
The purpose of this study was to describe the politeness of Indonesian between students and between students and teachers at SDN 06 Bengkulu City neighborhood. The research subject is that students of class V. The scope of this research is the use of verbal and nonverbal politeness by students at SDN 06 Bengkulu: students with students, and students with teachers. This type of research is qualitative descriptive. Data collected by observation, field notes, interview techniques and recording technique. Steps of data analysis conducted in stages, data reduction, data display and data verification. Results of research on linguistic politeness Indonesia students in the SDN 06 Bengkulu city, namely (1) for politeness the studentsdata found conversational politeness students more than the data conversation violation of politeness that is, 21 data is conversations that contain maxims of politeness and 5 the data conversation violation maxim of politeness, (2) for politeness between students and teachers found 7 data containing politeness conversation, and was not found students who violate the maxim of politeness and not found students against teachers. All data that conversation concluded with a look at the context of the speech that underlie the events said. The conclusion from this study is that politeness between students and between students and teachers reveal politeness. For nonverbal language, in speaking students use the fit between body language and speech (verbal).